2022
DOI: 10.1155/2022/9511492
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periodontal Endoscopy-Assisted Nonsurgical Treatment of Periodontitis: Four-Month Results of a Randomized Controlled Split-Mouth Pilot Study

Abstract: Objective. Although the therapeutic effects of nonsurgical periodontal therapy (NSPT) are well established, the clinical benefits of the additional use of periodontal endoscopy (PE) remain controversial. Therefore, this randomized controlled split-mouth pilot study evaluated the effect of NSPT using PE versus NSPT without nPE on bleeding on probing (BOP) in sites with probing depth (PD)≥4 mm (primary outcome), PD, clinical attachment level (CAL), number of hard deposits (HDs), and treatment time per tooth (TrT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…12 Graetz et al recently reported no differences in outcomes with and without the use of the periodontal endoscope at 4 months in their split-mouth randomized controlled study. 16 We report the results of nonsurgical periodontal therapy with or without the use of a periodontal endoscope in both anterior and posterior teeth for up to 1 year, which is a longer time period than reported by the aforementioned studies. However, we were limited by the sample size in our study, especially at 12 months.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…12 Graetz et al recently reported no differences in outcomes with and without the use of the periodontal endoscope at 4 months in their split-mouth randomized controlled study. 16 We report the results of nonsurgical periodontal therapy with or without the use of a periodontal endoscope in both anterior and posterior teeth for up to 1 year, which is a longer time period than reported by the aforementioned studies. However, we were limited by the sample size in our study, especially at 12 months.…”
Section: Discussionmentioning
confidence: 94%
“…Despite this, nonsurgical treatment can still result in a state of periodontal health. Some disadvantages of periodontal endoscopy were recently reported by Graetz et al 16 . Disadvantages include the requirement for special training and equipment, an association with a learning curve, and the requirement for additional treatment time, which could result in a higher cost to the patient.…”
Section: Discussionmentioning
confidence: 99%